Validating Instruments for Measuring Adaptive Intelligence: A Construct Validation Study of Five Components - Djiwandono, Patrisius Istiarto (International Journal of Asian Education, 2025)
This study aimed to validate instruments designed to measure the five components of adaptive intelligence, wisdom, creativity, problem-solving, analytical skills, and practical ability, and to identify the underlying factors of each construct. Adaptive intelligence is increasingly recognized as an essential competence for individuals to navigate rapidly changing environments, yet empirical studies that systematically validate its measurement tools remain limited. The study employed a quantitative validation design using exploratory factor analysis. Data were collected from 144 university students in Malang, Indonesia, selected through cluster sampling from a larger population. Five questionnaires, each consisting of 20 items, were developed in collaboration with expert lecturers to ensure content validity. Following a pilot test and revisions, the instruments were administered, and the data were analyzed using SPSS version 25 with Promax rotation and a loading threshold of 0.40. The results confirmed the multidimensional nature of adaptive intelligence. Wisdom was represented by three factors, creativity by two, problem-solving by three, analytical skills by three, and practical ability by four. These factor structures provide empirical evidence of adaptive intelligence's latent dimensions, highlighting its complexity as an integrated but multifaceted construct. The contribution of this study lies in both theoretical and practical domains. Theoretically, it advances the conceptual clarity of adaptive intelligence by specifying its latent dimensions. Practically, it provides validated instruments that educators and psychologists can employ to assess and foster adaptive capacities in students and professionals, supporting resilience and adaptability in diverse contexts.